The Effect of Circuit Training on Football Dribbling Skills (Experimental Study on the Student Football Activity Unit at One of the Universities) - Sigit Aryanto; Pungki Indarto; Nurhidayat, Nurhidayat (UNIB Press, 2024)
Football is a team sport in which players kick the ball back and forth while attempting to place the ball in the opponent's goal as soon as they can. Dribbling is a necessary football movement. The circuit training training model is one of the workouts used in an effort to increase dribbling accuracy. The aim of this research is to ascertain how UMS football UKM players' dribbling abilities are affected by training using the circuit training approach. The paired sample t-test analysis is the technique employed. The study's findings demonstrate the impact of circuit training activities on football players' dribbling abilities at the University of Muhammadiyah Surakarta's Football Student Activity Unit. The 2-tailed significance value, which displays a figure of 0.013 < 0.05 and indicates a significant difference between the pre- and post-test, provides evidence for this claim. Alternatively, based on the mean value, which is calculated by subtracting the exercise's value (13.4715) from the mean value (15.3260) prior to the circuit training session.Alternatively, based on the mean value, which is calculated by subtracting the exercise's value (13.4715) from the mean value (15.3260) prior to the circuit training session.